COMPARISON OF BIOPHARMACEUTICAL PARAMETERS OF CANNABINOIDS AND NON-STEROIDAL ANTI-INFLAMMATORY DRUGS BY QSAR METHOD - SYROESHKIN, ANTON V.; GALKINA, DARIA A.; OGOTOEVA, DAIAANA D.; LEVITSKAYA, OLGA V.; MOROZOVA, MARIYA A.; PLETENEVA, TATIANA V. (International Journal of Applied Pharmaceutics, 2023)
Objective: To prove the benefits of biopharmaceutical parameters of cannabinoids over NSAIDs using quantitative structure and activity relationships (QSAR). Methods: The topological indices of Wiener (W) and Balaban (J) were calculated using the previously developed original program ChemicDescript (certificate no. 2003612305). Results: It was shown that the calculated topological indices were in one-to-one correspondence with such biopharmaceutical parameters as the constants of equilibrium binding to cannabinoid receptors CB1 and CB2, toxicity, and lipophilicity. For example, it was shown that when the Wiener index changes from 480 to 530 LogK increases from 1.0 to 3.5. The LD50-W/J and logP-W/J diagrams demonstrate that cannabinoids are less toxic and more lipophilic than NSAIDs. Cannabidiol and cannabinol, having close values of their topological indices and insignificant psychoactivity, have the highest LD50 values, i.e. they are the least toxic. Moreover, for synthetic cannabinoids–nabilone and THJ-2201–the Wiener index is approximately 2 times higher than for plant analogues. Conclusion: In connection with the successful promotion of cannabinoid analgesics in the global pharmaceutical market, the results obtained are important for demonstrating their advantages over NSAIDs in terms of toxicity and lipophilicity. The results demonstrate the possibility of predicting the cannabinoid receptor binding energy of synthetic and newly identified plant cannabinoids, as well as assessing their toxicity and lipophilicity.